Analysis of scientific production on attributes of obstetric violence (Research, Society and Development, 2020)
Objective: To analyze the concepts and discussions on obstetric violence present in the scientific literature. Methodology: This is an integrative review type research, carried out between the months of July 2019 and January 2020. The searches were made operational based on the guiding question “what are the current concepts and discussions on obstetric violence present in the scientific literature? ”, In the Latin American and Caribbean Literature in Health Sciences databases; Medical Literature Analysis and Retrievel System Online and in the Nursing Database, through the Virtual Health Library. The Controlled Descriptors in Health Sciences were used, with intersections by Boolean operators: “Obstetric violence AND Violence against women” AND “Humanized delivery” OR “Health Education). Results: 12 articles were selected that were part of the final sample of this study. The points highlighted for discussion according to the studies analyzed were: Perception of puerperal women about obstetric violence; Most reported types of obstetric violence; Health professionals x Obstetric Violence. Conclusion: The studies analyzed bring the reality reported by women and health professionals in a systematic way by the authors. Thus, the proposed objective was reached in analyzing the concepts and discussions about obstetric violence, in the view of women and health professionals, which enriches the considerations on this theme that is still little addressed in the scientific literature. The consideration is given to the harmful effects of obstetric violence and the gaps that still refer to medical procedures and their indications.